1991
DOI: 10.1177/0013916591231002
|View full text |Cite
|
Sign up to set email alerts
|

Socioenvironmental Determinants of Community Formation

Abstract: Although environmental determinists have bemoaned the loss of community with increasing urbanization, other urban scholars have optimistically argued that urban characteristics provide increased opportunities for social interaction. Little research, however, has examined the relationship between urban characteristics and specific forms of community life, such as social support. Secondary data analyses were conducted on a sample of 442 public housing residents. This article suggests that socioenvironmental fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
1
15
0
2
Order By: Relevance
“…with facts that counter the myths (e.g., on average, people with mental illness are no more dangerous than the rest of the population). Although research suggests that these interventions might lead to mild change in attitudes (Holmes et al, 1999;Keane, 1991;Morrison, 1980;Penn et al, 1994) and limited change in behavior (Corrigan et al, in press), research has shown contact to yield the best changes in stereotypes, prejudice, and discrimination.…”
Section: How Contact Changes Stigmamentioning
confidence: 99%
“…with facts that counter the myths (e.g., on average, people with mental illness are no more dangerous than the rest of the population). Although research suggests that these interventions might lead to mild change in attitudes (Holmes et al, 1999;Keane, 1991;Morrison, 1980;Penn et al, 1994) and limited change in behavior (Corrigan et al, in press), research has shown contact to yield the best changes in stereotypes, prejudice, and discrimination.…”
Section: How Contact Changes Stigmamentioning
confidence: 99%
“…Crowded, dangerous, and noisy settings all appear to inhibit the formation of NSTs: Conditions of crowding and high-density living have been linked to poor social relations in a variety of communities (Keane, 1991;McCarthy & Saegert, 1978;Tbgnoli, 1987); settings in which there is high crime or high fear of crime are associated with a lack of neighborhood cohesion (Conklin, 1971;Rohe & Burby, 1988); and individuals are less likely to contribute to community activities in loud or noisy settings (S. Cohen & Lezak, 1977). Furthermore, Festinger, Schacter, and Back (1950) provided convincing evidence that two neighbors are most likely to form social ties with each other if they use the same semipublic access paths or staircases.…”
Section: The Role Of the Setting In The Development Of Neighborhood Smentioning
confidence: 99%
“…Furthermore, a number of recent cross-sectional studies on social networks in urban and non-urban areas show that people in both types of areas have many relations with their neighbours (e.g. Keane, 1991;Wellman, 1996;Thomese, 1998;Guest and Wierzbicki, 1999;Birenbaum-Carmeli, 1999). There is also other, less direct evidence suggesting that community still matters.…”
Section: Introductionmentioning
confidence: 99%